Noncommutative Geometry and Particle Physics - van Suijlekom, Walter D.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This book provides an introduction to noncommutative geometry and presents a number of its recent applications to particle physics. In the first part, we introduce the main concepts and techniques by studying finite noncommutative spaces, providing a (3z(Blight(3y (Bapproach to noncommutative geometry. We then proceed with the general framework by defining and analyzing noncommutative spin manifolds and deriving some main results on them, such as the local index formula. In the second part, we show how noncommutative spin manifolds naturally give rise to gauge theories, applying this principle to specific examples. We subsequently geometrically derive abelian and non-abelian Yang-Mills gauge theories, and eventually the full Standard Model of particle physics, and conclude by explaining how noncommutative geometry might indicate how to proceed beyond the Standard Model. The second edition of the book contains numerous additional sections and updates. More examples of noncommutative manifolds have been added to the first part to better illustrate the concept of a noncommutative spin manifold and to showcase some of the key results in the field, such as the local index formula. The second part now includes the complete noncommutative geometric description of particle physics models beyond the Standard Model. This addition is particularly significant given the developments and discoveries at the Large Hadron Collider at CERN over the last few years. Additionally, a chapter on the recent progress in formulating noncommutative quantum theory has been included. The book is intended for graduate students in mathematics/theoretical physics who are new to the field of noncommutative geometry, as well as for researchers in mathematics/theoretical physics with an interest in the physical applications of noncommutative geometry.s
Finite noncommutative spaces -- Finite real noncommutative spaces -- Noncommutative Riemannian spin manifolds -- The local index formula in noncommutative geometry -- Gauge theories from noncommutative manifolds -- Spectral invariants -- Almost-commutative manifolds and gauge theories -- The noncommutative geometry of electrodynamics -- The noncommutative geometry of Yang-Mills fields -- The noncommutative geometry of the Standard Model -- Phenomenology of the noncommutative Standard Model -- Towards a quantum theory.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Mathematical physics; Algebraic geometry; Particles (Nuclear physics).; Mathematical Physics; Algebraic Geometry; Particle Physics